Effects of ammonia-ambient annealing on physical and electrical characteristics of rare earth CeO2 as passivation film on silicon - Hock, Jin Quah; Hassan, Zainuriah; Fong, Kwong Yam; Ahmed, Naser Mahmoud; Mohd Salleh, Mohammad Amran; Matori, Khamirul Amin; Lim, Way Foong (Elsevier, 2017)
Effects of post-deposition annealing at 400–1000 °C in ammonia (NH3) gas ambient towards physical and electrical characteristics of metal-organic decomposition derived CeO2 films spin-coated on n-type Si substrates were studied. The use of NH3 annealing as N and H sources has promoted nitridation and passivation occurring at interface between the CeO2 and Si. Mixed oxidation states (Ce4+ and Ce3+) were detected in the samples via the detection of CeO2 and Ce2O3 phases, confirmed using high resolution X-ray diffraction analysis, Raman, and Fourier Transform Infrared studies. An increase in nitridation effect with respect to temperature has impeded the formation of Ce2Si2O7 interfacial layer (IL) while the enhancement of passivation effect has triggered a decrease in interface trap density. Corresponding effects towards metal-oxide-semiconductor characteristics of the samples were discussed in details.